Pengaruh Lama Penyimpanan Benih dan Konsentrasi Rendaman Air Kelapa terhadap Viabilitas Benih Padi (Oryza sativa L.) - NI KADEK INDRI SUSILIASTANA PUTRI; IDA AYU PUTRI DARMAWATI; I NYOMAN GEDE ASTAWA (Fakultas Pertanian Universitas Udayana, 2023)
Effect of Seed Storage Time and Coconut Water Soak Concentration on Viability of Rice Seed (Oryza sativa L.). This study aims to determine the effect of seed storage time and concentration of coconut water immersion on viability of rice seeds (Oryza sativa L.). This study used a completely randomized design (CRD) split plot. The main plot is the storage time of seeds consisting of 3 levels, namely storage time of 7 months (L1), 8 months (L2) and 9 months (L3). Sub-plots were the concentration of coconut water immersion consisting of 4 levels, namely immersion without coconut water (K0), 10% coconut water (K1), 20% coconut water (K2) and 30% coconut water (K3). Each treatment was repeated three times. This research was carried out at the Plant Breeding and Seed Technology Laboratory, Faculty of Agriculture, Udayana University from October 2021 to December 2021. The results showed a storage period of 7 months and a concentration of 10% coconut water (L1K1) which had the highest growth rate of 84.00% compared to with a storage period of 9 months and without soaking coconut water (L3K0) which has the lowest value of simultaneous growth of 52.00%. The storage period of 7 months gave the highest value for the variables of growth speed (23.96%/etmal), simultaneous growth (79.42%), germination (96.17%) and maximum growth potential (97.42%) compared to storage time. 8 and 9 months. The 10% coconut water concentration gave the highest value for the variable growth speed (23.65%/etmal) and maximum growth potential (96.44%) compared to no coconut water immersion. The concentration of 30% gave the highest value for the simultaneous growth variable (75.22%) compared to no coconut water immersion.